PENINGKATAN KUALITAS GURU DI INDONESIA: TANTANGAN DAN UPAYA PEMECAHANNYA MELALUI KEBIJAKAN - Agus Susanto; Shinta Diana; Hauna Aprilia Mumtahanah; Wahyudin Wahyudin; Defi Tri Mulyani; Pirdaus Alandes (Hijri, 2025)
Improving teacher quality is a strategic element in improving the quality of national education. However, various structural and systemic challenges still hinder the optimization of teachers' roles in Indonesia. This study aims to identify the main challenges in improving teacher quality and analyze the efforts made through government policies to address these challenges. The research method used is library research, involving the review of various academic literature, policy documents, and relevant research reports. The results of the study show that the main challenges include disparities in teacher competencies and qualifications, uneven distribution of teachers, especially in 3T (frontier, outermost, and disadvantaged) areas, lack of continuous professional training and development, high administrative burdens, and low teacher welfare and motivation. Analysis of government policies indicates that despite the existence of various programs such as teacher certification, the Teacher Development Program, and the digitization of training, their implementation still faces numerous obstacles. In conclusion, improving teacher quality requires more holistic, integrated, and sustainability-oriented policies, as well as equitable access to professional development.